Limitation of the single-domain numerical approach: Comparisons of analytical and numerical solutions for a forced convection heat transfer problem in a composite duct - Kuznetsov, Andrey V. (Computer Assisted Methods in Engineering and Science, 2023)
The aim of this paper is to establish the bounds of applicability of the single-domain numerical approach for computations of convection in composite porous/ fluid domains. The large number of papers that have utilized this numerical approach motivates this research. The popularity of this approach is due to the simplicity of its numerical formulation. Since the utilization of the single-domain numerical approach does not require the explicit imposing of any boundary conditions at the porous/ fluid interface, the aim of the this research is to investigate whether this method always produces accurate numerical solutions.